Holistic Christian spirituality and health - Zyzak, Wojciech (Psychoonkologia, 2018)
Spirituality is recognised as a factor that contributes to health in many persons. The concept of spirituality is found in all cultures and societies. The effect of spirituality on health is an area of active research right now. Besides being studied by physicians, it is studied by psychologists and other professionals, for example theologians. The author of the article discusses the impact of Christian spirituality on human health from a holistic point of view. For this purpose he introduces the holistic idea of spirituality, which is based on integral anthropology, understanding a human being as spiritual-corporal unity. The text underlines the connection between nature and grace, sacred and profane, individual and community.